Electron-nuclear dynamics in noble metal nanoparticles - Senanayake, Ravithree Dhaneeka (Kansas State University, 2018)
Thiolate-protected noble metal nanoparticles (~2 nm size) are efficient solar photon harvesters, as they favorably absorb within the visible region. Clear mechanistic insights regarding the photo-physics of the excited state dynamics in thiolate-protected noble metal nanoclusters are important for future photocatalytic, light harvesting and photoluminescence applications. Herein, the core and higher excited states lying in the visible range are investigated using the time-dependent density functional theory method for different thiolate-protected nanoclusters. Nonadiabatic molecular dynamics simulations are performed using the fewest switches surface hopping approach with a time-dependent Kohn-Sham (FSSH-TDKS) description of the electronic states with decoherence corrections to study the electronic relaxation dynamics. Calculations on the [Au₂₅ (SH)₁₈]⁻¹ nanocluster showed that relaxations between core excited states occur on a short time scale (2-18 ps). No semiring or other states were observed at an energy lower than the core-based S₁ state, which suggested that the experimentally observed picosecond time constants could be core-to-core transitions rather than core-to-semiring transitions. Electronic relaxation dynamics on [Au₂₅ (SH)₁₈]⁻¹ with different R ligands (R = CH₃, C₂H₅, C₃H₇, MPA) [MPA = mercaptopropanoic acid] showed that all ligand clusters including the simplest SH model follow a similar trend in decay within the core states. In the presence of higher excited states, R= H, CH₃, C₂H₅, C₃H₇ demonstrated similar relaxations trends, whereas R=MPA showed a different relaxation of core states due to a smaller LUMO+1-LUMO+2 gap. Overall, the S₁ state gave the slowest decay in all ligated clusters. An examination of separate electron and hole relaxations in the [Au₂₅ (SCH₃)₁₈]⁻¹ nanocluster showed how the independent electron and hole relaxations contribute to its overall relaxation dynamics. Relaxation dynamics in the Au₁₈(SH)₁₄ nanocluster revealed that the S₁ state has the slowest decay, which is a semiring to core charge transfer state. Hole relaxations are faster than electron relaxations in the Au₁₈(SH)₁₄ cluster due its closely packed HOMOs. The dynamics in the Au₃₈(SH)₂₄ nanocluster predicted that the slowest decay, the decay of S₁₁ or the combined S₁₁-S₁₂, S₁-S₂-S₄-S₇ and S₄-S₅-S₉-S₁₀ decay, involves intracore relaxations. The phonon spectral densities and vibrational frequencies suggested that the low frequency (25 cm⁻¹) coherent phonon emission reported experimentally could be the bending of the bi-icosahedral Au₂₃ core or the “fan blade twisting” mode of two icosahedral units. Relaxation dynamics of the silver nanoparticle [Ag₂₅ (SR)₁₈]⁻¹ showed that both [Ag₂₅(SH)₁₈]⁻¹ and [Au₂₅ (SH)₁₈]⁻¹ follow a common decay trend within the core states and the higher excited states.
Keywords: Gold and silver nanoparticles; Excited state dynamics; Nonadiabatic; Nonradiative dynamics; Time-dependent Kohn Sham description